FACTORS INFLUENCING THE IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEM IN SMALL-MEDIUM ENTERPRISES IN PURWOKERTO - Anggun Tya Priyati; Agung Praptapa; Rini Widianingsih (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This research examines the influence of accounting training, business scale, business age, educational background on the intention to use of accounting information systems and the influence of the intention to use and level of education on implementation accounting information system using Planned Behavior Theory. The data of this study was carried out by the quatory method and using primary data. The sample was determined using the proportionate stratified random sampling method which amounted to 61 SMEs. The data is processed by using the SPSS version 19 application for windows. The results of this study show that (1) Accounting training has no positive effect on the intention to use of accounting information system in SMEs, (2) The business scale has a positive effect on the intention to use of the accounting information system in SMEs, (3) Business Age has no positive effect on the intention to use of the accounting information system in SMEs, (4) The level of education has positive effect on the intention to use of the accounting information system in SMEs, (5) The interest in using have a positive effect on the implementation of accounting information system in SMEs (6) Education level has positive effect on the implementation of accounting information system in SMEs.